The Comparison of a New Ultrasound-Induced Depression Model to the Chronic Mild Stress Paradigm - Zorkina, Yana A.; Zubkov, Eugene A.; Morozova, Anna Yu.; Ushakova, Valeriya M.; Chekhonin, Vladimir P. (Frontiers in Behavioral Neuroscience, 2019)
Willner’s “chronic mild stress” (CMS) model is a globally recognized and most commonly used depression model. A depression model induced by ultrasonic exposure of variable frequencies has been created in our laboratory. This article compares two models of the depressive-like state according to three validity criteria. Face validity has been demonstrated in sucrose preference test, Porsolt test, social interest, open field and the Morris water maze. Rats after ultrasound impact have more pronounced anhedonia and social isolation. The construct validity has been proven due to increased levels of corticosterone, epinephrine and norepinephrine and reduced levels of dopamine and some of its metabolites in rat plasma after ultrasound exposure. Predictive validity has been described previously, where the therapeutic effects of various classes of antidepressants have been shown. Our study has demonstrated that the ultrasound-induced depression model is suitable, such as the generally accepted CMS protocol, and meets all required validity criteria. The model presented in this article might help to study pathogenetic mechanisms of depressive disorders, as well as to test promising methods of depression treatment.